2018
DOI: 10.1007/s11136-018-1966-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of untreated dental caries severity on the quality of life of preschool children and their families: a cross-sectional study

Abstract: Severe untreated dental caries with clinical consequences had a negative impact on the children's OHRQoL, regardless of toothache and socioeconomic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
76
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 36 publications
9
76
1
6
Order By: Relevance
“…Our results corroborate the evidence that untreated caries has ramifications not just for oral health but also for the general health of the affected children 20,21 . The burden of ECC and its impacts beyond the clinical aspects suggest the need to address specific strategies to improve dental health in childhood.…”
Section: Discussionsupporting
confidence: 88%
“…Our results corroborate the evidence that untreated caries has ramifications not just for oral health but also for the general health of the affected children 20,21 . The burden of ECC and its impacts beyond the clinical aspects suggest the need to address specific strategies to improve dental health in childhood.…”
Section: Discussionsupporting
confidence: 88%
“…Se podría considerar que al no ser evaluadas las lesiones cavitadas código 5 y 6 de ICDAS, no obtuvieron manifestación clínica visiblemente complejas lo que indica que para la percepción de sus padres no fue perjudicial en su calidad de vida. Respecto a la percepción de responsabilidad de los padres por la presencia de caries dental, Cesarino M. et al (20) , hallaron que esta aumenta con la aparición avanzada de la enfermedad, lo cual conlleva a necesitar tratamientos urgentes, como también lo refiere Vieira -Andrade R. et al (21) , Wong S. et al (22) y Correa -Faria P. et al (23) , sobre las consecuencias de caries no tratadas, que presentaron impacto negativo en preescolares, sobre la percepción de responsabilidad y preocupación de los padres o cuidador Arrow P. (24) encontró ausencia de responsabilidad y poca importancia en el cuidado de los dientes deciduos, así como también un desconocimiento sobre tratamientos preventivos, resultado que no coincide con los obtenidos en este estudio ya que al realizar la evaluación del ECOHIS hubieron padres que manifestaron estar preocupados por la salud bucal de su hijo, aunque al realizar el examen clínico no se corroboró dicha aseveración, ya que habían muchos niños enfermos.…”
Section: Discussionunclassified
“…World Health Organization (WHO) reported that approximately 60-90% of adult and almost 100% of children experienced untreated dental caries 1) . In 2016, The estimated burden for treatments of caries in the US was almost 124 billion USD 2,3) . The most commonly used restorative materials include dental amalgam, resin composites, and glass ionomer cements (GICs).…”
Section: Introductionmentioning
confidence: 99%